Preliminary validation of treatment relationship confirmed by event log applications - Tuula Ristimäki; Maria Pohjanvuori; Ari Pätsi (Finnish Social and Health Informatics Association, 2015)
A relationship between patients and healthcare professional should be confirmed by an EHR system before the patients' medical records are made available to healthcare professionals. We have earlier presented a logical level description about how a connection between patients and healthcare professionals (i.e. a treatment relationship) could be established automatically by event log applications (SIEM) after patient data has been accessed via an EHR system or other applications. The purpose of this study was to analyze, if the data collected for automatic confirmation of treatment relationships by SIEM was valid and to decrease the need for manual analysis. The record access data was collected from various information systems for the event log analyzer. The analyzing principles established in this case were based on the hospital's core processes. The outcome substantiates the view that automation can be used to evaluate large numbers of events. There is, however, still the need to further specify and apply principles to the configuration, in order to improve the surveillance within indirect use of patient information.